Empowerment of health cadres in early detection and family-based stunting prevention - Fitri Anita; Mery Kana; Evi Nurmaisa Biduri (Edukasi Ilmiah Indonesia, 2025)
Stunting remains a significant public health issue that affects children’s growth and development, with long-term consequences for cognitive capacity, productivity, and overall quality of life. One effective strategy to overcome this issue is through the empowerment of health cadres as the frontline in early detection and family-based prevention efforts. This community service program aims to enhance the role and capacity of health cadres in identifying risk factors, conducting routine monitoring, and implementing preventive measures to address stunting within families. The method applied includes training, mentoring, and participatory workshops, focusing on knowledge improvement and practical skills related to nutrition, growth monitoring, and family education. Health cadres are also equipped with communication skills to enhance awareness and behavior change among parents, thereby fostering a supportive environment for children’s optimal growth. The results show increased knowledge and confidence of cadres in identifying early signs of stunting, as well as improved community participation in monitoring children’s nutritional status. Furthermore, family engagement in preventive practices, such as providing a balanced diet and maintaining hygiene, demonstrated a significant enhancement. This initiative demonstrates that empowering health cadres not only enhances early detection but also promotes sustainable, family-based stunting prevention. Therefore, community-based health empowerment is a strategic approach that can contribute substantially to reducing stunting prevalence and improving child health outcomes in the long term.